Important Aspects Of Strategic Development Of Parents And Preschool Education Organization (Eurasian Journal of Learning and Academic Teaching, 2024)
Currently, changes and innovations are being introduced in pre-school education organizations. Modern preschool educational organizations have the opportunity to use all the various forms of interaction between the kindergarten and the family, which have come a long way in their formation and development. Parents and preschool education organization are not interchangeable. An important condition of continuity is the establishment of reliable business relations between parents and preschool education organization, during which the educational position of parents and educator-pedagogue is adjusted. The basis of such relations is the form of mutual relations between parents and preschool education organization.